Foreign Studies of the Neuropsychological and Biological Bases of Aggressive Behavior - K.M. Shipkova; S.V. Shport; V.G. Bulygina (Психология и право)
The paper analyzes the data of empirical studies on the relationship between the evolution and involution of aggressive behaviour and the level of neurocognitive functioning. The specificity of the neuropsychological picture of regulatory dysfunction in individuals prone to reactive and proactive aggression is discussed. The article raises the question of the role of memory disorders in the evolution of aggressive behaviour. The paper presents constellations of cognitive, behavioural and neurodynamic deficits in individuals vulnerable to different types of aggression. The review shows that the significance of the research results in understanding the structural components of executive functions is substantiated. The paper describes the biological basis of aggressive behaviour and the influence of an aggressive environment on the occurrence of aggressive behaviour. The article indicates prospects of studying the interaction between the factors affecting the prodrome of aggressive behaviour and types of neuropsychological syndromes of executive functions impairment.